Retinotopic activation in response to subjective contours in primary visual cortex - Maertens, Marianne; Pollmann, Stefan; Hanke, Michael; Mildner, Toralf; Möller, Harald E. (Frontiers in Human Neuroscience, 2008)
Objects in our visual environment are arranged in depth and hence there is a considerable amount of overlap and occlusion in the image they generate on the retina. In order to properly segment the image into fi gure and background, boundary interpolation is required even across large distances. Here we study the cortical mechanisms involved in collinear contour interpolation using fMRI. Human observers were asked to discriminate the curvature of interpolated boundaries in Kanizsa fi gures and in control confi gurations, which contained identical physical information but did not generated subjective shapes. We measured a spatially precise spin-echo BOLD signal and found stronger responses to subjective shapes than non-shapes at the subjective boundary locations, but not at the inducer locations. The responses to subjective contours within primary visual cortex were retinotopically specifi c and analogous to that to real contours, which is intriguing given that subjective and luminance-defi ned contours are physically fundamentally different. We suggest that in the absence of retinal stimulation, the observed activation changes in primary visual cortex are driven by intracortical interactions and feedback, which are revealed in the absence of a physical stimulus.